Empirical investigation of indoor environmental quality (IEQ) performance in hospital buildings in Nigeria - Nimlyat, Pontip Stephen (Penerbit UTM Press, 2015)
This study investigates and summarises the results of physical measurement of the indoor environmental quality (IEQ) in hospital building wards in Plateau State, Nigeria comparing two hospital settings. The results indicate that the mean indoor air temperature in the case study hospital ward buildings exceeded the range of 23-26 °C as recommended by international standards. The temperature levels in the teaching hospital ward buildings were relatively lower than what was obtained in the specialist hospital whose ward buildings lack proper ventilation. The amount of daylight requirement on an average were below 300Lux in the specialist hospital whose façade orientation and window-wall-ratio (WWR) could not allow for maximum sunlight penetration, while it was above 300Lux in the teaching hospital. However, the sound intensity level in both hospital ward buildings ranged between 52.7dBA and 71.3dBA. This study therefore recommend that, hospital building design or retrofitting should employed common strategies towards increasing ventilation and daylight with minimal energy consumption.